Surface chemistry for cytosolic gene delivery and photothermal transgene expression by gold nanorods - Hirotaka Nakatsuji (Nature Portfolio, 2017)
Abstract Light-inducible gene regulation has great potential for remote and noninvasive control of the fate and function of target cells. One method to achieve such control is delivery of heat shock protein (HSP) promoter-driven protein expression vectors and photothermal heaters into the cells, followed by activation by illumination. In this study, we show that gold nanorods (AuNRs) functionalized with two conventional lipids, oleate and 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP), are capable of efficient transfection and quick photoactivation of the HSP promoter. Use of our AuNRs (DOTAP-AuNRs) was comparable to Lipofectamine 2000 in terms of transfection efficiency, while lower in cytotoxicity. Subsequent near-infrared laser (NIR) illumination of the cells transfected by DOTAP-AuNRs for 10 s induced time- and site-specific transgene expression without significant phototoxicity, to a degree similar to that of heating the entire culture dish for 30 min. Our mechanistic studies suggest that efficient transfection and quick photoactivation of the HSP promoter (HSP70b’) are due to the promoted endosomal escape of DOTAP-AuNRs. We propose a novel protocol for NIR-inducible, site-directed gene expression using an unprecedented complex of the three conventional components capable of both transfection and photothermal heating.